European investment programs in the economy of Ukraine: horizon Europe program - Moroz, Karyna; Pererva, P. G. (Кременчуцький національний університет імені Михайла Остроградського, 2024)
The report proves that the European Union (EU) and individual European countries have been actively supporting Ukraine's economy, especially since the beginning of the war in 2022. Investment programs are aimed at recovery, infrastructure modernization, development of small and medium-sized businesses (SMEs), as well as green energy and digital transformation.
Європейські інвестиційні програми в економіці України: програма "Горизонт Європа"
Keywords: economy of Ukraine; European Union; war; aid; investment programs